Odvijanje preje z navitka - obravnava kinematičnih in dinamičnih lastnosti preje - Praček, Stanislav (Strojniški vestnik, 2005)
We discuss yarn unwinding from packages, which is of chief importance in many textile processes. We derive a very general system of differential equations that describe the motion of the yarn during unwinding. We discuss the physicalmeaning of individual terms in the equations with special emphasis on virtuals forces, which appear in rotating coordinate systems. We also show howthe equations can be numerically solved in the quasistationary approximation in order to obtain an image of yarn in space during unwinding.
Keywords: gibanje preje; lastnosti kinematične; lastnosti dinamične; enačbe diferencialne; odvijanje preje; simulacije; matematični modeli